Exploring factors influencing individual participation in community‐based tourism: The case of Kampung Relau homestay program, Malaysia - Kayat, Kalsom (2002)
This paper presents the early findings from a qualitative investigation conducted to examine how participation is practiced in a community‐based tourism program which offers homestay experience to tourists in Kedah, Malaysia.The first objective of the study was to determine where on the spectrum of participation (Pretty 1995) does the homestay program fall. The second objective was to explore the variables that may influence the extent of community participation in this program. Findings from the present study indicate that participation in community‐based tourism is influenced by community members’ motivations to participate. An important implication from this finding is that community‐based tourism projects must include awareness programs among its members so as to educate them about the project and to motivate them to participate.